2002
DOI: 10.1152/jn.2002.87.6.3090
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the Thalamic CM-Pf Complex in Attentional Orienting

Abstract: The centre médian-parafascicular (CM-Pf) complex is located at the posterior intralaminar nuclei of the thalamus and forms part of the nonspecific thalamocortical projection system and the internal circuit of the basal ganglia. However, the functional roles of this complex remain to be fully elucidated. Here we have examined whether the CM-Pf complex is involved in the process of covert attention. We trained two macaque monkeys to perform a task in which a visual target stimulus for button release appeared at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(143 citation statements)
references
References 55 publications
2
139
1
1
Order By: Relevance
“…Pf neurons project mostly to the caudate nucleus and putamen situated rostral to the anterior commissure, whereas CM neurons project to the posterior part of the putamen (Sadikot et al, 1992). Neurons in the CM-Pf complex respond to multimodal stimuli, especially those presented on the contralateral side to which monkeys paid selective attention (Minamimoto and Kimura, 2002). This evidence could explain the contralateral preference of TAN responses in the caudate nucleus to visual instructions for saccade task (Shimo and Hikosaka, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Pf neurons project mostly to the caudate nucleus and putamen situated rostral to the anterior commissure, whereas CM neurons project to the posterior part of the putamen (Sadikot et al, 1992). Neurons in the CM-Pf complex respond to multimodal stimuli, especially those presented on the contralateral side to which monkeys paid selective attention (Minamimoto and Kimura, 2002). This evidence could explain the contralateral preference of TAN responses in the caudate nucleus to visual instructions for saccade task (Shimo and Hikosaka, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, previous electrophysiological studies have documented the heterogeneity of cells in the Pf nucleus based on differences in their responsiveness to different sensory afferent inputs (Matsumoto et al, 2001;Minamimoto and Kimura, 2002). A further differentiation between 'noxious-on' and 'noxious-off' cell types has been reported in rat Pf (Liu et al, 1993).…”
Section: Conclusion Heterogeneity Of Electrophysiological Propertiesmentioning
confidence: 89%
“…It is also known that inactivation of this input eliminates both the pause and rebound activation of TANs (Matsumoto et al, 2001). By the way of thalamic inputs, it has been suggested that the cholinergic interneurons are in the position to supply the striatum with signals related to attention (Matsumoto et al, 2001;Minamimoto and Kimura, 2002;Ding et al, 2010). Thus, in the search for the origin of prediction error signals in TANs, it remains to determine the extent to which TAN response components might encode some form of attention.…”
Section: Discussionmentioning
confidence: 99%